Antibiotic Susceptibility and Resistance Genes in Oral Clinical Isolates of Prevotella intermedia, Prevotella nigrescens, and Prevotella melaninogenica - Yormaris Castillo; Nathaly Andrea Delgadillo; Yineth Neuta; Andrés Hernández; Tania Acevedo; Edwin Cárdenas; Andrea Montaño; Gloria Inés Lafaurie; Diana Marcela Castillo (MDPI AG, 2022)
The Prevotella genus is a normal constituent of the oral microbiota, and is commonly isolated from mechanically treated polymicrobial infections. However, antibiotic treatment is necessary for some patients. This study compared the antibiotic susceptibility and the presence of resistance genes in clinical oral isolates of P. intermedia, P. nigrescens, and P. melaninogenica. Antibiotic susceptibility was assessed using the agar dilution method. PCR confirmed the species and resistance gene frequency in the Prevotella species. The frequencies of species P. intermedia, P. nigrescens, and P. melaninogenica were 30.2%, 45.7%, and 24.1%, respectively. No isolates of P. intermedia were resistant to amoxicillin/clavulanic acid, tetracycline, or clindamycin. P. nigrescens and P. melaninogenica were resistant to amoxicillin/clavulanic acid and tetracycline at frequencies of 40% and 20%, respectively. P. intermedia was resistant to metronidazole at a frequency of 30%, P. nigrescens at 20%, and P. melaninogenica at 40%. P. nigrescens and P. melaninogenica were resistant to 50% and 10% clindamycin, respectively. The gene most frequently detected was tetQ, at 43.3%, followed by tetM at 36.6%, blaTEM at 26.6%, ermF at 20%, cfxA, cfxA2, and nimAB at 16.6%, and nimAEFI at 3.3%. P. nigrescens was the species with the highest resistance to antibiotics such as amoxicillin/clavulanic acid, amoxicillin, and clindamycin, in addition to being the species with the largest number of genes compared to P. intermedia and P. melaninogenica.